Trauma patients with lower extremity and pelvic fractures: Should anti-factor Xa trough level guide prophylactic enoxaparin dose?. (March 2018) - Dhillon, Navpreet K.; Smith, Eric J.T.; Gillette, Emma; Mason, Russell; Barmparas, Galinos; Gewertz, Bruce L.; Ley, Eric J.
Abstract: Background: Adequate venous thromboembolism (VTE) prophylaxis is essential after trauma, especially in patients with lower extremity and/or pelvic fractures. We sought to investigate if prophylactic enoxaparin dosed by anti -Xa trough levels could reduce clinically evident VTE in trauma patients with lower extremity or pelvic injury. Methods: Prospective data was collected on trauma patients admitted for at least two days with any lower extremity and/or pelvic fracture and who received enoxaparin for VTE prophylaxis between October 2013 and January 2016. Patients in the control cohort received enoxaparin at 30 mg twice daily. Patients in the adjustment cohort had anti -Xa trough levels measured after three or more consecutive doses of enoxaparin. Those with a trough level of 0.1 IU/mL or lower had their dosage increased by 10-mg increments. Results: Of the 159 patients included, 58 (36.5%) were monitored with anti -Xa trough levels. The cohorts were similar in age, sex, regional AIS, ISS score, ICU and hospital length of stay, proportion of patients with diagnostic testing for VTE, and time to first enoxaparin dose. Initial enoxaparin dosing in the majority of patients (84.5%) who had anti -Xa trough levels measured was subprophylactic. Patients receiving enoxaparin dosed by anti -Xa trough level had a significantly lower VTE rate than those who did not (1.7% v. 13.9%, p = 0.03). Conclusions: Prophylactic enoxaparin adjusted by anti -factor Xa level may lead to a decreased rate of clinically evident VTE among trauma patients with lower extremity and/or pelvic fractures. Our findings indicate that the initial dose of enoxaparin was frequently too low. Highlights: Adequate VTE prophylaxis is essential after trauma. The VTE risk is higher in patients with extremity and/or pelvic fractures. The role of using anti -Xa trough levels in dosing enoxaparin is unknown. This strategy is associated with a decrease in VTE rates in this population.